2021
DOI: 10.21037/atm-21-3668
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of fucoidan purified from Undaria pinnatifida against UV-irradiated skin photoaging

Abstract: Background: Exposure to ultraviolet (UV) radiation (UVB and UVA) is the most well-known extrinsic factor that induces skin aging. Fucoidan has been shown to possess antiphotoaging effects against UV irradiation and can be used as an ingredient in the pharmaceutical industry. The present study evaluated the photoprotective effect of fucoidan purified from Undaria pinnatifida (UPF) on UV-induced skin photoaging and explored its potential molecular mechanism.Methods: To evaluate the effect of UPF on UV-induced sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…79 Studies proved that UVA-irradiation decreased the activation of the AMPK/ SIRT-1/PGC-1α pathway in HaCaT cells and HFF-1 cells. 80 The present study also found the mRNA and protein expression of AMPK, SIRT-1, and PGC-1α decreased in UVB-induced skin damage. Other research using human dermal fibroblasts and a 3D skin model to evaluate the effect of Aquatide on UV-induced skin aging found that Aquatide upregulated the expression of FOXO1 by activating the expression of SIRT-1.…”
supporting
confidence: 77%
“…79 Studies proved that UVA-irradiation decreased the activation of the AMPK/ SIRT-1/PGC-1α pathway in HaCaT cells and HFF-1 cells. 80 The present study also found the mRNA and protein expression of AMPK, SIRT-1, and PGC-1α decreased in UVB-induced skin damage. Other research using human dermal fibroblasts and a 3D skin model to evaluate the effect of Aquatide on UV-induced skin aging found that Aquatide upregulated the expression of FOXO1 by activating the expression of SIRT-1.…”
supporting
confidence: 77%
“…Fucoidan is a sulfated polysaccharide found in large quantities in the cell wall. It has the potential to be employed as an antioxidant, anticancer, anti-angiogenic, antiphotoaging and antitumor drug, according to several in vitro investigations (Cong et al 2016;Jing et al 2021;Palanisamy et al 2018; Shannon et al 2021;Shen et al 2017). Mannitol is a monosaccharide found in the cytoplasm of brown seaweeds.…”
Section: Brown Seaweedsmentioning
confidence: 99%
“…The low-molecular-weight fucoidan and its derivatives show high antioxidant capacity [ 31 ]. Although some studies reported that the functional properties of sulfated polysaccharides failed to characterize the structural properties [ 28 ], fucoidan refined from marine algae was widely studied in in vitro skin care studies [ 14 , 17 , 32 , 33 ]. Specifically, the anti-inflammatory effect of fucoidan on FD-stimulated epidermal cells [ 14 ], the mixture of TNF-α and IFN-γ-stimulated epidermal cells [ 17 ], and the antioxidative effect of fucoidan on UVB-stimulated epidermal cells [ 32 , 33 ] were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies reported that the functional properties of sulfated polysaccharides failed to characterize the structural properties [ 28 ], fucoidan refined from marine algae was widely studied in in vitro skin care studies [ 14 , 17 , 32 , 33 ]. Specifically, the anti-inflammatory effect of fucoidan on FD-stimulated epidermal cells [ 14 ], the mixture of TNF-α and IFN-γ-stimulated epidermal cells [ 17 ], and the antioxidative effect of fucoidan on UVB-stimulated epidermal cells [ 32 , 33 ] were reported. The anti-inflammatory mechanism of fucoidan via cyclooxygenase 2 (COX2) inhibition [ 34 ], NF-κB signaling inhibition in the Wistar rat models [ 35 ], MAPK signaling inhibition in cerebral ischemia-reperfusion injured rat model [ 36 ], and regulating chemokines and cytokines secretion [ 17 ] were identified in recent studies.…”
Section: Discussionmentioning
confidence: 99%